A marca na moda jovem: a relevância da experiência colateral na eficácia comunicativa da marca - Almeida, Mariane Tojeira Cara (2007)
The identity of Fashion brand, especially in young universe, is build by several information that are beyond the commercialized clothes. To understand the complexity and therefore to get more knowledge about this phenomena, the present research intends to analyze the relevance of Collateral Experience - theoretical concept from Charles Sanders Peirce in his Theory of Signs - to build an identity to brands. In this case, Collateral Experience is what assigns a previous knowledge with the symbolic meaning of brands, mainly in teenager age. This kind of previous knowledge is developed by various contacts with diverse mass media and other media systems used in everyday life by youth. The research corpus was mainly defined from analysis of recent researches, as Dossiê Universo Jovem 3 from MTV music channel and Retratos da Juventude Brasileira, report organized by Helena Wendel Abramo who presents the current situation of youth in Brazil. To give account of considered subject, the applied methodology was based in non-racionalist Peircean semiotics. The stages of this research includes bibliographical survey about main subjects, as theoretical basement of Peircean concepts through his writings and writings from his interpreters; studies from Fashion theoreticians, also books and papers about Marketing and Media, as well as analysis of the recent research above cited, other related researches and pragmatic observation of the fact. Given the increasing attention destined to studies that involves brands, the present work shows relevance in Communication and Fashion area, raising questions about consumption behavior in generation who has been born in later 80 s and early 90 s, those who grew in front of TV and were plugged and connected in Internet since their first years of life, showing the great relevance of cyber culture and media to get information and knowledge, also in Fashion scope